Combination therapy for optimum glycaemic control : a randomized open label trial comparing rosiglitazone with combination sulphonylureas and metformin tablets in type 2 diabetes mellitus - Ghazali, Wan Syamimee Wan (2006)
Background As it is often difficult to achieve and maintain glycaemic goals, multiple drug therapy is eventually required in most patients. Combination therapy, involving an insulin secretagogue and an insulin sensitizer, can address the metabolic effect of this disease. The use of two sensitizers with different but complementary mechanisms of action may provide additional glucose control. The addition of thiazolidinedione may Improve glycaemic control in patients who failed to achieve glycaemic control with a combination of sulphonylureas and metformin. There is scarce data on efficacy, safety and cost effectiveness of adding third agent to patients who failed to achieve glycaemic control on maximum combination therapy. Objectives To determine the efficacy, safety and cost effectiveness of adding Rosiglitazone to patients with type 2 diabetes mellitus on maximum dose of sulphonylureas and metformin who had not achieved glycaemic controlResearch design and methodology This was a randomized, open label study. The subjects with T2DM who refused insulin therapy were randomized into treatment group and control group. The treatment group received adding a dose of rosiglitazone 4 mg once daily for 6 months while the control group was maintained on maximum dose of metformin and sulphonylureas. HbAlc, FBS, Total Cholesterol, LDL and HDL were taken at baseline and at 6 month. Results A total of 75 diabetic patients were included in this study. There was significant reduction in HbAlc ( 9.61 ± 1.37% to 8.20 ± 1.87% ; p < 0.001 ) and FBS ( 9.6 ± 3.69 mmoliL to 7.93 ± 3.46mmol/L; p = 0.002) in treatment group after 6 months of therapy. However, in control group, there was a significant increased in HbAlc (9.75 ± 1.33 % to 10.06 ± 1.77%; p = 0.023) but no significant change in FBS (10.81 ± 3.38mmol/L to 10.48 ± 3.29 mmoliL ; p = 0.95) at 6 months. There was greater reduction in HbA 1 c level and FBS in treatment group compared to control group - 1.3 7 % vs + 1. 70 % and - 0.24 % vs + 0.41 % respectively. Twenty eight percent (28 % ; p < 0.001) (11 I 40) of patients ofthe treatment group achieved HbA1c < 7% while no one in control group achieved this target. For FBS, 51 % ( p < 0.001) (19 I 37) of patients in the treatment group achieved FBS < 7mmol/l compared with the controlgroup, only 12 % (3 I 25) of patients achieved FBS < 7 mmol/1 at 6 months. There were no significant changes in lipid profiles at 6 months in both groups. In addition, for every improvement of 1 o/o HbA1c, there was 13.3 times better chance in improvement of HbA1c (OR 13.3, adjusted 17 ). The cost effectiveness (CE) ratio between the treatment and the control group was not significant (z =- 0.79, p= 0.43) Conclusion The addition of rosiglitazone improves glycaemic control, when compared to patients in control group, allowing more patients to achieve HbA1c < 7 % with greater reduction of HbA 1 c. In addition, adding rosiglitazone to patients on maximum metformin and sulphonylureas were efficacious but not cost effective.